Microbial Diversity and Community Structure in Alpine Stream Soil. Issue 3 (1st March 2021) - Rasool, Atta; Ali, Salar; Ali, Waqar; Eldesoky, Gaber E.; Shafeeque, Muhammad; Ahmad, Iftikhar; Akram, Muhammad; Tahir, Muhammad; Muhammad, Said; Nasim, Wajid
Abstract: Investigations of microbial communities over arsenic-polluted soils in an alpine stream are vital to collect pieces of evidence for their in situ -mediated bioremediation. It is the first time that microbial community activities are described in arsenic-polluted soils due to natural and anthropogenic sources along the alpine stream. Greater than 40 phyla from domain bacteria the 16S rRNA Illumina sequencing amplicons are exposed. In overall samples, Unweighted Pair Group Method with Arithmetic Mean (UPGMA) states that the most dominant phyla were Proteobacteria, Cyanobacteria, and Actinobacteria . Our result described that canonical correspondence analysis was used to elaborate more geochemical factors including arsenic, sulfate, total organic carbon, redox potential, and pH influence on the distribution of microbial groups in studies soil samples. Furthermore, Spearman's rank correlation demonstrates a positive correlation between several specific taxonomic groups, refers to the phylotypes' possible role in arsenic biogeochemical cycling. The present research could link the knowledge gap and facilitate our understanding for the bioremediation of arsenic at contaminated sites. Highlights: We described the microbial communities in arsenic-contaminated soils. CCA revealed that chemical parameters organized microbial communities. The effects of geochemical conditions on microbial community composition were examined.